God as father: the representation of the tenth plague in children's Bibles - J. S. du Toit (Acta Theologica)
The Book of Exodus’ account of the ten plagues as moment of Israelite liberation from Egyptian servitude is particularly poignant. The troublesome nature of the story’s climax — the slaying of the firstborn — proves difficult to relate to a contemporary child audience in light of the nature and seeming injustice of the punishment meted out to their innocent peers. Along with the death of all Egyptian firstborn, Israelite deliverance is ultimately attained by the inclusion of even the pharaoh’s own son in this final act of devastation. The latter’s death through the direct agency of God presents a problematic perspective on the portrayal of the deity as loving father in light of the anti-hero, Pharaoh’s, loss. This article investigates children’s Bibles’ multiple approaches to this narrative. It is considered in light of current societal emphasis on non-violent behaviour and as commentary on the manner in which contemporary society negotiates moral-ethical quandaries in the transfer of religious meaning to children.